You are on page 1of 6

# Proceedings of the AMATYC 33rd Annual Conference, Minneapolis, Minnesota 2007

## Techniques on Partial Fractions

Tingxiu Wang, Ph.D.
Professor of Mathematics
Oakton Community College
1600 East Golf Road, Des Plaines, IL 60016
Phone: 847-635-1751, Email: tingxiu@oakton.edu
Abstract: Since graphing calculators (such as TI-89) and computer algebra systems can do
Partial Fraction Decomposition (PFD), some teachers pay less attention on PFD. Although PFD
is quite technical, we believe PFD also enable students to learn mathematical ideas and methods.
Recently, there have been some papers discussing about PFD [1, 2, 3]. The standard method of
PFD is the Method of Undetermined Coefficients (MUC), with which the calculation is often
tedious. However, we can formulize the process of partial fractions, and then all calculations of
partial fractions simply are related to three formulas. In addition, PFD obtained by MUC is often
not ready for integration. We proposed a different format of PFD that can be for immediate
integration. The techniques discussed here have not been found in textbooks, and these
alternative techniques can inspire students to explore and understand partial fractions.

## 1. Techniques on Partial Fraction Decomposition

Technique 1: All decompositions of partial fraction can be done by applying the following three
formulas:
Formula I:

1
1
1
1

, a b
=

[ p ( x) + a][ p( x) + b] b a p( x) + a p( x) + b

Formula II:

1
( x a )( x + bx + c)
2

1 1
x+a+b

f (a) x a
f ( x)

## where f ( x) = x 2 + bx + c and f (a) 0 .

x+m+
1
1
x+m+b
,
2
=
2
2
( x + x + )( x + bx + c) ( b) f 1 (m) x + x + x + bx + c
c
, f1 ( x) = x 2 + x + , and f1 (m) 0 .
where b , m =
b

Formula III:

Technique 2: When we integrate a rational function, we can break the rational function into
partial fractions in terms of derivatives of denominators:

Tingxiu Wang

## Proceedings of the AMATYC 33rd Annual Conference, Minneapolis, Minnesota 2007

American Mathematical Association of Two Year Colleges, http://www.amatyc.org/

factorable in real numbers and a 0 , then we can have the following partial fractions:
An f ( x) + Bn
A1 f ( x) + B1 A2 f ( x) + B2
+
+

+
.
f ( x)
f 2 ( x)
f n ( x)

2. Proof of Formulas

1
1
1
1

, a b.
=

[ p( x) + a][ p( x) + b] b a p( x) + a p( x) + b
Formula I was discussed in [3] by Huang and examples can be found there. The next two
formulas have not been seen in any publications.
1
1 1
x+a+b

,
=

Formula II.
2
f ( x)
( x a )( x + bx + c) f (a) x a
Formula I.

## where f ( x) = x 2 + bx + c and f (a) 0 .

Proof of Formula II by derivation: Let
x+
1

=
+ 2
.
2
( x a )( x + bx + c) x a x + bx + c
Then the numerators satisfy

1 = ( x 2 + bx + c) + ( x + )( x a ).
1
Take x = a, then 1 = (a 2 + ab + c) = f (a), or =
.
f (a)
1
c
1
Take x = 0, then 1 = c a =
c a , so =
.
f (a)
af (a) a
Take x = 1, then 1 = (b + c + 1) + ( + )(1 a), or

1=
Solve for , we get =

c
1
1
(1 a ).
(b + c + 1) + +
f (a )
af (a) a

1
. Therefore
f (a)
1

( x a )( x + bx + c)
2

c
1
1
x+

f (a)
af (a) a
2
x + bx + c

1
1
+
f (a) x a

x+a+b
1 1

f (a) x a
f ( x)

x+m+
1
x+m+b
1
2
,
2
=
2
( x + x + )( x + bx + c) ( b) f1 (m) x + x + x + bx + c
c
, f1 ( x) = x 2 + x + , and f1 (m) 0 .
where b , m =
b

Formula III.

Tingxiu Wang

## Proceedings of the AMATYC 33rd Annual Conference, Minneapolis, Minnesota 2007

American Mathematical Association of Two Year Colleges, http://www.amatyc.org/

## Remark 2.1. Switching the positions between f1 ( x) = x 2 + x + and f 2 ( x) = x 2 + bx + c

in the above formula implies that f 2 (m) 0 . We can switch the positions of f1 ( x) and f 2 ( x) if
evaluating f 2 (m) is easier. If = b , people can apply Formula I.
Proof of Formula III by derivation. Let the fraction have the following decomposition:

1
x+u
x+v
,
2
= A 2
2
2
( x + x + )( x + bx + c)
x + x + x + bx + c
where A, u, v are undetermined coefficients. By completing the subtraction of the right hand
side, we get
1 = A [(b + u v) x 2 + (c + ub v ) x + uc v ].
Therefore
(1)
uv+b = 0

ub v + c = 0 (2)
A(uc v ) = 1
(3)

1
. Multiplied by b, Equation (1) becomes
uc v
ub vb + b 2 b = 0 (4)
Equation (4) minus Equation (2), we get v( b) + b 2 b c + = 0 , or

b2 b c +
c
=b+
, and
b
b
c
c
u = v+ b = b+
+ b = +
.
b
b

c
c
c b +

uc v = +
b
b

v=

= c b +

c
(c )
b

= c bc + bc b +

(c ) 2 ( b)
( b) 2

c
c
+ ( b)b
= ( b)
+ ( b)c
b
b
= ( b) f 1 ( m)
c
= x+m+
b
c
= x+m+b
x+v = x+b+
b
x+u = x+ +

Therefore

Tingxiu Wang

## Proceedings of the AMATYC 33rd Annual Conference, Minneapolis, Minnesota 2007

American Mathematical Association of Two Year Colleges, http://www.amatyc.org/

x+u
x+v
1

= A 2
2
2
( x + x + )( x + bx + c)
x + x + x + bx + c
x+m+b
1 x+m+
2

=
2
uc v x + x + x + bx + c
This completes the proof of Formula III.
2

## Proof of Formula III by Verification.

x+m+
1
x+m+b
2

2
( b) f1 (m) x + x + x + bx + c
=

m ( c ) + c b
1

2
2
( b) f1 (m) ( x + x + )( x + bx + c)

m(c ) + c + b
1

( b) f1 (m) ( x 2 + x + )( x 2 + bx + c)

m(c ) + (c ) + ( b )
1
2
( b) f 1 ( m)
( x + x + )( x 2 + bx + c)

c
1 c
1
+ 2
+
m
2
f 1 ( m) b
b
( x + x + )( x + bx + c)
1
= 2
.
( x + x + )( x 2 + bx + c)

3. Examples

1
1
1
=
2
( x 3x + 4)(2 x x + 1) 2 ( x 2 3x + 4)( x 2 1 x + 1 )
2
2
1
1
c 7
= and f1 ( x) = x 2 3x + 4 .)
(by Formula III, let = 3 , = 4 , b = , c = , m =
2
2
b 5
Example 3.1.

7 1
7
x + + (3) x + +

1
1
5 2
2 5
=

5
44
1
2
( x 3 x + 4) 2 1

x x +

2 25
2
2

8
9

x
x+

5
10
5
=
1
1
44 x 2 3 x + 4
x2 x +

2
2

Tingxiu Wang

## Proceedings of the AMATYC 33rd Annual Conference, Minneapolis, Minnesota 2007

American Mathematical Association of Two Year Colleges, http://www.amatyc.org/

## Remark 3.2. Partial fraction decomposition is considered complete if it only contains

A
Bx + C
and 2
, where m and n are positive integers and
expressions like
m
( x a)
( x + bx + c) n

## x 2 + bx + c is prime in real numbers.

3x 2 + 4 x + 4 3x 2 + 4 x + 4
=
Example 3.2.
x3 + 4x
x( x 2 + 4)

Example 3.3.

## (factoring the denominator)

3( x 2 + 4) 12 + 4 x + 4
=
(plus 12 and minus 12)
x( x 2 + 4)
3
4
8
= + 2

(decomposition)
2
x x + 4 x( x + 4)
x
3
4
1
(by Formula III)
= + 2
2 2

x x +4
x x + 4
1 2x + 4
= + 2
x x +4
x
x +11
=
(plus 1 and minus 1)
2
2
( x + 1)( x + x + 2)
( x + 1)( x 2 + x + 2) 2
1
1
1
2
(separating the fractions)
= 2
2
( x + x + 2)
( x + x + 2) ( x + 1)( x 2 + x + 2)
1
1
x 1+1
1 1
2
= 2
2

## (by Formula II)

2
( x + x + 2)
( x + x + 2) 2 x + 1 x + x + 2
1
1
1
x
1

+
= 2
2
2
2
2 ( x + 1)( x + x + 2) 2 ( x + x + 2) 2
( x + x + 2)
1
x 1+1 1
x
1 1 1
= 2
(by Formula II)

+
2
2
2 2 x + 1 x + x + 2 2 ( x + x + 2) 2
( x + x + 2)
x
1 1 1
1
1
x

+
.
=
+ 2
+ 2
2
2
4 x + 1 4 x + x + 2 ( x + x + 2)
2 ( x + x + 2) 2

## 4. Integration by Partial Fractions in Terms of the Derivative of a Factor

The common format of partial fractions with a quadratic factor, (ax 2 + bx + c) n , which is
not factorable in real numbers, is
An x + Bn
A1 x + B1
A2 x + B2
.
(1)
+
++
2
2
2
ax + bx + c (ax + bx + c)
(ax 2 + bx + c) n
But integrating a rational function with this format, students can still be frustrated because it is
not ready for integration. For example, by decomposing the rational function,
3
3
x +1
x 1
2
2
(2)
( x 2 + 2 x + 2)( x + 2)dx = x 2 + 2 x + 2 x + 2 dx .
Techniques on Partial Fractions

Tingxiu Wang

## Proceedings of the AMATYC 33rd Annual Conference, Minneapolis, Minnesota 2007

American Mathematical Association of Two Year Colleges, http://www.amatyc.org/

3
x +1
2
Many students still have difficulties to finish 2
dx . Almost all calculus textbooks use
x + 2x + 2
this format of partial fractions. To make the decomposition ready for integration by substitution,
I taught students with an alternative format:
If the denominator has a factor, (ax 2 + bx + c) n , where f ( x) = ax 2 + bx + c is not factorable in
real numbers and a 0 , then we can have the following partial fractions:
A f ( x) + Bn
A1 f ( x) + B1 A2 f ( x) + B2
+
++ n n
.
(3)
2
f ( x)
f ( x)
f ( x)
Formats (1) and (3) are equivalent. But (3) has the following advantages:
It is ready for integration by substitution.
Finding undetermined coefficients of (3) is easier than (1) because we can use the zero
of f ' ( x) .
x 1
dx .
Let us revisit Equation (2): find 2
( x + 2 x + 2)( x + 2)
Solution:

x 1
A(2 x + 2) + B
C
+
= 2
x+2
x + 2x + 2
( x + 2 x + 2)( x + 2)
2

x 1 = [ A(2 x + 2) + B ](x + 2) + C (x 2 + 2 x + x )
3
Let x = 2 , 3 = 2C , C = .
2
3
1
Let x = 1 (the zero of f ' ( x) ), 2 = B + C , or 2 = B , and B = .
2
2
3
Let x = 0 , 1 = 2(2 A + B ) + 2C , A = .
4
Thus,
x 1
2x + 2
1
1
3 1
3
( x 2 + 2 x + 2)( x + 2)dx = 4 x 2 + 2 x + 2 2 x 2 + 2 x + 2 2 x + 2 dx ,
and the integral can be finished more effectively than (2).
Reference:

1. Brazier, Richard and Boman, Eugene (2007), How to Compute the Partial Fraction
Decomposition Without Really Trying, The AMATYC Review, Vol. 29, No.1, 20-29.
2. Cherif, Chokri (2007), An Alternative Method to the Classical Partial Fraction
Decomposition, The AMATYC Review, Vol. 29, No.1, 31-37.
3. Huang, XunCheng (1991), A Shortcut in Partial Fractions, College Mathematics Journal,
Vol. 22, No.5, 413415.

Tingxiu Wang